2012
DOI: 10.1111/j.1365-2036.2012.05011.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: cardiovascular safety profile of 5‐HT4 agonists developed for gastrointestinal disorders

Abstract: SummaryBackgroundThe nonselective 5-HT4 receptor agonists, cisapride and tegaserod have been associated with cardiovascular adverse events (AEs).AimTo perform a systematic review of the safety profile, particularly cardiovascular, of 5-HT4 agonists developed for gastrointestinal disorders, and a nonsystematic summary of their pharmacology and clinical efficacy.MethodsArticles reporting data on cisapride, clebopride, prucalopride, mosapride, renzapride, tegaserod, TD-5108 (velusetrag) and ATI-7505 (naronapride)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
215
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(227 citation statements)
references
References 188 publications
3
215
1
4
Order By: Relevance
“…However, there are several systematic reviews and meta-analyses evaluating the role of prucalopride [59][60][61][62][63][64][65][66][67][68] in the management of chronic constipation and their findings are consistent with the findings of the current study. Although the scope of the current article is the evaluation of clinical effectiveness and adverse events related to prucalopride only, previously reported systematic reviews [59][60][61][62][63][64][65][66][67][68] have reported its safety, efficacy, pharmacokinetics, and tolerability providing supporting evidence to our conclusions. As reported by Tack et al 69 "Prucalopride is an important addition to the therapeutic abilities for treating chronic constipation, especially in females poorly responding to laxatives.…”
Section: Discussionsupporting
confidence: 82%
“…However, there are several systematic reviews and meta-analyses evaluating the role of prucalopride [59][60][61][62][63][64][65][66][67][68] in the management of chronic constipation and their findings are consistent with the findings of the current study. Although the scope of the current article is the evaluation of clinical effectiveness and adverse events related to prucalopride only, previously reported systematic reviews [59][60][61][62][63][64][65][66][67][68] have reported its safety, efficacy, pharmacokinetics, and tolerability providing supporting evidence to our conclusions. As reported by Tack et al 69 "Prucalopride is an important addition to the therapeutic abilities for treating chronic constipation, especially in females poorly responding to laxatives.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, gastric ulceration was significantly relieved and the hexosamine content of gastric mucus was significantly increased, as were the gastric mucosal levels of PGE2 (12,17). However, cisapride is associated with adverse cardiovascular events and has therefore been replaced by mosapride, a novel selective 5-HT4 receptor agonist with safer profiles (18,19). A study by Fujisawa et al (11) found that treatment with a low dose of mosapride inhibited gastric mucosa injury induced by indomethacin, and their results showed that 0.5 mg/kg mosapride was the optimal dose.…”
Section: Discussionmentioning
confidence: 94%
“…The serious cardiac adverse events (palpitations, myocardial infarction, ventricular fibrillation, torsades de pointes and sudden death) and medication interactions that led to the withdrawal of the less selective serotonergic agonists cisapride and tegaserod have not been observed with prucalopride. 71 The comparative effectiveness of prucalopride versus the more commonly recommended osmotic agent PEG was recently evaluated in a single center RCT from Romania. 72 Two hundred and forty CIC patients received either PEG 3350 and electrolytes (26 g) or prucalopride (1-2 mg) for 28 days.…”
Section: Serotonin Receptor Modulatorsmentioning
confidence: 99%